2018
DOI: 10.1515/shll-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

El castellano del Caribe colombiano en la ciudad de Nueva York: El uso variable de sujetos pronominales

Abstract: ResumenEste estudio de la expresión de pronombres personales de sujeto entre hablantes del castellano caribeño colombiano en Nueva York revela una tasa pronominal (43 %) significativamente más alta que la existente en el Caribe colombiano. Los resultados descubren que cinco predictores lingüísticos y dos sociales condicionan la expresión pronominal. Los predictores lingüísticos – entre los cuales persona y número del sujeto condiciona más fuertemente el uso pronominal – revelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 43 publications
1
21
0
2
Order By: Relevance
“…Silva-Corvalán (1988) incorporates motion verbs to this classification (andar 'walk,' caminar 'walk,' corer 'run,' etc.). This classification has been implemented-in some cases with minor adaptations-in many studies which have shown the conditioning effect of the verb on SPE (e.g., Cerrón-Palomino 2014; Erker and Guy 2012;Hurtado 2001Hurtado , 2005bOrozco 2015aOrozco , 2018aOrozco , 2018bTravis 2005aTravis , 2005bTravis , 2007among others). General verb type tendencies show that cognitive and perceptive verbs favor overt subjects (Silva-Corvalán and Enrique-Arias 2017, p. 175) whereas all other verbs-especially desiderative and other verbs-favor null subjects.…”
Section: Previous Treatments Of the Effect Of The Verb On Spementioning
confidence: 99%
See 4 more Smart Citations
“…Silva-Corvalán (1988) incorporates motion verbs to this classification (andar 'walk,' caminar 'walk,' corer 'run,' etc.). This classification has been implemented-in some cases with minor adaptations-in many studies which have shown the conditioning effect of the verb on SPE (e.g., Cerrón-Palomino 2014; Erker and Guy 2012;Hurtado 2001Hurtado , 2005bOrozco 2015aOrozco , 2018aOrozco , 2018bTravis 2005aTravis , 2005bTravis , 2007among others). General verb type tendencies show that cognitive and perceptive verbs favor overt subjects (Silva-Corvalán and Enrique-Arias 2017, p. 175) whereas all other verbs-especially desiderative and other verbs-favor null subjects.…”
Section: Previous Treatments Of the Effect Of The Verb On Spementioning
confidence: 99%
“…Since its inception into pronombrismo by Enríquez (1984), the lexical content of the verb classification has been used by many scholars, most notably Zentella (2007, 2012) in their monumental study of SPE in New York City Spanish. The detailed lexical content description provided by Otheguy and Zentella (2012) in their SPE coding manual -a pronombrista guidebook which they generously shared ahead of its publication-prompted many other researchers (Carvalho and Child 2011;Erker and Guy 2012;Flores-Ferrán 2002Orozco 2015aOrozco , 2016Orozco , 2018aOrozco , 2018bOrozco and Guy 2008;among others) to explore the effect of verbs on SPE using this classification. Overall, the lexical content of the verb tendencies tell us that (a) stative verbs favor overt subjects; (b) both mental activity verbs and estimative verbs moderately favor overt subjects-this explains why many studies have examined these two types of verbs jointly (e.g., Erker and Guy 2012; Otheguy and Zentella 2012; Orozco and Guy 2008; among others); and (c) external activity verbs favor null subjects.…”
Section: Lexical Content Of the Verbmentioning
confidence: 99%
See 3 more Smart Citations